PENGEMBANGAN BOOKLET BERBASIS QR CODE PADA MATERI PENGUKURAN PANJANG DENGAN SATUAN BAKU KELAS III-A SDN KETETANG 1 BANGKALAN - Haya Zahra; Mohammad Edy Nurtamam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to develop a QR Code-based booklet on length measurement material with a valid, attractive, and effective standard unit of class III-A elementary school Ketetang 1. This research uses the 4D model development method (Define, Design, Development, Disseminate). The subjects of this study are 31 students in grade III-A elementary school Ketetang 1. This development research uses data collection techniques such as observation, interviews, questionnaires, and tests. The results of the study show that the QR Code-based booklet product developed has been declared valid, attractive, and effective. The validity of the product was assessed by several experts, namely material experts at 92.5%, learning design experts at 98.21%, teaching material experts at 92.5%. The three validation results are included in the "very valid" category. The attractiveness of the product was assessed by the limited test teacher response questionnaire of 93% while the implementation test was 100%, and the limited test student response questionnaire was 96.89%, while the implementation test was 91.98%. The results earned the category of "very interesting". The effectiveness of the product was assessed by observation of the activities of the limited test students of 81.81%, while the implementation test was 88.98%. Observation of teacher activity is limited test and implementation test is 100%. The results of the student learning test were limited trials and implementation was 100%. The results earned the category of "highly effective".